Primeros registros de poblaciones silvestres de Musa velutina (Musaceae, Zingiberales) en Colombia - Giraldo-Cañas, Diego (2024)
Musa velutina H. Wendl. & Drude, a native species from Asia, is recorded for the first time for Colombia. Its description, popular names, uses, geographical and ecological distribution, and some in vivo photographs are given.